2008
DOI: 10.1021/ic7023296
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Study of the Spectroscopic and Redox Properties of RuII,PtII Mixed-Metal Complexes Bridged by 2,3,5,6-Tetrakis(2-pyridyl)pyrazine

Abstract: The mixed-metal supramolecular complexes [(tpy)Ru(tppz)PtCl](PF6)3 and [ClPt(tppz)Ru(tppz)PtCl](PF6)4 (tpy = 2,2':6',2''-terpyridine and tppz = 2,3,5,6-tetrakis(2-pyridyl)pyrazine) were synthesized and characterized. These complexes contain ruthenium bridged by tppz to platinum centers to form stereochemically defined linear assemblies. X-ray crystallographic determinations of the two complexes confirm the identity of the metal complexes and reveal intermolecular interactions of the Pt sites in the solid state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 56 publications
4
26
0
Order By: Relevance
“…The pyridyl rings at the uncoordinated side of the tppz ligand are planar within experimental errors but the tppz ligand as a whole is far from being planar due to the steric effects between the hydrogen atoms at the 3-pyridyl positions. Low energy conformations of tppz are predicted to have each pyridyl ring twisted from coplanarity with the pyrazine by roughly 50° [24][25][26]. For the coordinated side of the tppz ligand, the dihedral angle between the mean planes of the two coordinated pyridyl rings is 3.92(1)°, whereas that between the two uncoordinated pyridyl rings is 48.75(11)°.…”
Section: Synthesismentioning
confidence: 99%
“…The pyridyl rings at the uncoordinated side of the tppz ligand are planar within experimental errors but the tppz ligand as a whole is far from being planar due to the steric effects between the hydrogen atoms at the 3-pyridyl positions. Low energy conformations of tppz are predicted to have each pyridyl ring twisted from coplanarity with the pyrazine by roughly 50° [24][25][26]. For the coordinated side of the tppz ligand, the dihedral angle between the mean planes of the two coordinated pyridyl rings is 3.92(1)°, whereas that between the two uncoordinated pyridyl rings is 48.75(11)°.…”
Section: Synthesismentioning
confidence: 99%
“…These complexes are unique in their coupling of LA units to a Pt(II) center in a stereochemically defined coordination environment. The crystal structures of the two complexes have previously been reported [22]. Both complexes display distorted octahedral geometry around the Ru center and distorted square planar geometry around the Pt center with the proposed tridentate bridging coordination of the tppz ligand.…”
Section: Resultsmentioning
confidence: 89%
“…Sodium dihydrogen phosphate was obtained from Acros Organics. The metal complexes [(tpy)Ru(tppz)PtCl](PF 6 ) 3 and [ClPt(tppz)Ru(tppz)PtCl] (PF 6 ) 4 , were prepared according to previously reported procedures [22]. Electrophoresis was performed using an Owl Separation Systems, Inc. (Portsmouth, NH) Model B1A electrophoresis stage at 104 V ($35 mA) for 1.5 h. Gels were then stained with 0.5 lg/mL ethidium bromide for 45 min followed by 45 min of destaining in double distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…The emission maximum of compound 42+ is slightly blue‐shifted relative to that of [(bpy) 2 Ru(dpdpzH)PtCCPh] 2+ , in accordance with their absorption spectra, as shown in Figure 5. It has been reported that the excited‐state lifetime of bis‐tridentate ruthenium complexes can be prolonged by forming a two‐metal system, which stabilizes the ligand π*‐acceptor orbital and lowers the MLCT state below the deactivating ligand‐field state 24. However, previous TDDFT results have shown that the lowest MLCT transitions are mainly associated with the platinum‐acetylide component.…”
Section: Resultsmentioning
confidence: 98%